Prevention of neurological complications during COVID-19: a retrospective analysis of the ISARIC4C national cohort. Issue 9 (12th August 2022) - Grundmann, Alexander; Hardwick, Marc; Wu, Chieh-Hsi; Semple, Malcolm; Böhning, Dankmar; Pett, Sarah; Michael, Benedict; Thomas, Rhys; Galea, Ian
Abstract : Neurological complications occur in 4% of patients following acute COVID-19 infection, causing significant morbidity with lasting health economic consequences. However treatment studies to date in COVID-19 have not addressed neurological complications as outcome measures. We therefore performed a retrospective, non-interventional cohort study using the ISARIC-4C platform, assessing 62, 729 hospital inpatients with severe COVID-19 between 31 Jan 2020 and 29 Jun 2021. Treatment with dexamethasone, remdesivir or both was compared to standard of care. The primary outcome was a neurological complication, namely stroke, seizure, meningitis/encephalitis or any other neurological complication, occurring at the point of death, discharge, or resolution of the COVID-19 clinical episode. A propensity scoring methodology was used to balance confounding between treatment groups and between patients with and without neurological complications. Treatment with dexamethasone, remdesivir or both reduced the incidence of neurological complications from severe COVID-19, with odds ratios of 0.76 (0.69-0.83), 0.68 (0.51-0.90) and 0.64 (0.56 -0.72) respec- tively. Neurological complications were associated with increased length of hospital stay, worse ability to self-care on discharge and increased mortality. This study is the first to focus on the prevention of neurological complications and strongly supports the continued use of both dexamethasone and remdesivir in severe COVID-19. Our results suggest that the established benefit of dexamethasone on mortality in COVID-19 is not associated with an increased burden of long-term neurological disability.